2002
DOI: 10.1103/physrevb.65.233404
|View full text |Cite
|
Sign up to set email alerts
|

Tensor LEED analysis of theNi(111)(3×3)R30°Pb

Abstract: The structure of the Ni(111)()ϫ))R30°-Pb surface has been determined by quantitative low-energy electron diffraction ͑LEED͒, using multiple-scattering simulations of the measured diffracted beam intensities with a tensor-LEED program. The results confirm that the surface comprises a single-layer substitutional alloy of stoichiometry Ni 2 Pb ͑with all atoms in ''fcc'' sites relative to the underlying Ni͒ and clearly excludes a surface/subsurface stacking fault ͑with occupation of ''hcp'' sites͒ like that found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…This amplitude of the 'rumpling' is smaller by about 1 Å than that predicted by a simple touching hard-spheres model based on bulk metallic radii (1.44 Å for Ag and 1.80 Å for Pb). This suggests a reduction in the effective radii similar to that found by Quinn et al [6] in their LEED study of the substitutional surface alloy structure for the Pb-Ni(111) system. It has been suggested that the reduction in the effective radii may be attributed to the influence of valence electron charge smoothing and associated surface stress effects [5,24,6,13].…”
Section: Parametersupporting
confidence: 81%
See 1 more Smart Citation
“…This amplitude of the 'rumpling' is smaller by about 1 Å than that predicted by a simple touching hard-spheres model based on bulk metallic radii (1.44 Å for Ag and 1.80 Å for Pb). This suggests a reduction in the effective radii similar to that found by Quinn et al [6] in their LEED study of the substitutional surface alloy structure for the Pb-Ni(111) system. It has been suggested that the reduction in the effective radii may be attributed to the influence of valence electron charge smoothing and associated surface stress effects [5,24,6,13].…”
Section: Parametersupporting
confidence: 81%
“…This suggests a reduction in the effective radii similar to that found by Quinn et al [6] in their LEED study of the substitutional surface alloy structure for the Pb-Ni(111) system. It has been suggested that the reduction in the effective radii may be attributed to the influence of valence electron charge smoothing and associated surface stress effects [5,24,6,13]. A similar effect is possibly the case for the Pb-Ag(111) structure in our study.…”
Section: Parametersupporting
confidence: 81%
“…It is commonly agreed that R P values below 0.2 indicate an excellent agreement between experimental and theoretical I(V) curves, whereas values above 0.3 are interpreted as mediocre fits. Excellent refinements yielding very low R P values in the range 0.11-0.24 were reported for complex inorganic surface structures such as CoO(111), 48 GaN(0001), 49 and BaFe 2 As 2 (001) 50 as well as surface alloys or metal superstructures on metals like Pb/Ni(111), 51 Sn/Ni(110), 52 Sn/Ni(111), 53 Sb/Cu(110), 54 and Au/Pd(100). 55 Moreover, relatively simple atomic superstructures could also be refined with high accuracy, examples comprise hydrogen on Ir(110), 56 (R P = 0.10) and halogens on metal surfaces such as Cl/Ru(0001) 57 and Br/Pt(110) 58 with R P = 0.19 and 0.23, respectively.…”
Section: Resultsmentioning
confidence: 80%
“…The study of the growth and morphology of thin and submonolayer films composed of heavy elements of group IV on semiconductor and metal substrates receives much attention from both experimental and theoretical perspectives. 1–13 To date, it has been established using various methods that the submonolayer adsorption of heavy elements on the substrates results in the formation of two-dimensional surface phases. 1–3,14,15 This can be either an adlayer consisting only of adatoms or a surface alloy.…”
Section: Introductionmentioning
confidence: 99%